2003
DOI: 10.1016/s0531-5565(02)00146-8
|View full text |Cite
|
Sign up to set email alerts
|

Calorie restriction in rhesus monkeys

Abstract: Calorie restriction (CR) extends lifespan and reduces the incidence and age of onset of age-related disease in several animal models. To determine if this nutritional intervention has similar actions in a long-lived primate species, the National Institute on Aging (NIA) initiated a study in 1987 to investigate the effects of a 30% CR in male and female rhesus macaques (Macaca mulatta) of a broad age range. We have observed physiological effects of CR that parallel rodent studies and may be predictive of an inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
163
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(175 citation statements)
references
References 72 publications
(89 reference statements)
8
163
0
4
Order By: Relevance
“…The age-related changes in plasma testosterone, triglycerides, oxidative damage and glucose regulation could be attenuated by CR, 37,38 which is related to autophagic activation. 39 Sitzmann et al 40 reported that moderate CR could help maintain higher levels of circulating testosterone.…”
Section: Discussionmentioning
confidence: 94%
“…The age-related changes in plasma testosterone, triglycerides, oxidative damage and glucose regulation could be attenuated by CR, 37,38 which is related to autophagic activation. 39 Sitzmann et al 40 reported that moderate CR could help maintain higher levels of circulating testosterone.…”
Section: Discussionmentioning
confidence: 94%
“…brain maturation could be compared at similar ages in calorically restricted and normal model organisms. In support of this view, the effects of caloric restriction show a decrease in the normal rate of maturation in both rodents (Kalu et al, 1984;Merry & Holehan, 1981) and rhesus monkeys (Mattison et al, 2003). Interestingly, caloric restriction seems to have reduced effects on longevity if applied after middle age, i.e.…”
Section: Caloric Restrictionmentioning
confidence: 85%
“…De plus, le déclin des fonctions immunitaires lié à l'âge, l'atrophie de la matière grise cérébrale, ainsi que l'apparition de sarcopénie ont également été atténués chez les animaux soumis à une restriction calorique [12]. Cette dernière induit chez les primates une diminution de la masse corporelle, une réduction de la masse grasse, mais également celle de la température corporelle par comparaison avec des animaux contrôles du même âge [13]. Cependant, l'impact de la restriction calorique sur les fonctions reproductrices des primates est moins clair.…”
Section: Médecine/sciencesunclassified
“…Chez les primates, l'augmentation de la sensibilité aux infections par des pathogènes ou le ralentissement du processus de cicatrisation n'ont pas encore été étudiés. Chez les macaques, la restriction calorique à long terme affecte négativement la minéralisation osseuse [14] et l'axe neuroendocrine de la reproduction [13]. Chez l'homme aussi, des effets délétères ont été rapportés, comme une diminution de la densité osseuse [34].…”
Section: Et Chez L'homme ?unclassified